On some integral operator - Korobeinik, J. F. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ю. Ф. Коробейник. Об одном интегральном оператореJ. F. Korobeinikas. Vieno integralinio operatoriaus klausimu